263TiPATHENA (GOG-3020/ENGOT-ov45): A randomised, double-blind, placebo-controlled phase III study of the poly (ADP-ribose) polymerase (PARP) inhibitor rucaparib + the PD-1 inhibitor nivolumab following frontline platinum-based chemotherapy in ovarian cancer. (24th November 2019) - Fujiwara, K; Chou, H-H; Kim, J-W; Tan, D S; Tamura, K; Katsumata, N; Harano, K; Hasegawa, K; Hume, S; Jones, E; Goble, S; Sullivan, L; et al.
Abstract: Background: Rucaparib has clinical activity in patients with recurrent ovarian cancer with or without homologous recombination deficiency (HRD; eg, a BRCA mutation or high genome-wide loss of heterozygosity) and is hypothesised to provide clinical benefit following frontline treatment. ATHENA (NCT03522246) is evaluating rucaparib + nivolumab as maintenance treatment following frontline platinum-based chemotherapy in patients with newly diagnosed, high-grade ovarian, fallopian tube, or primary peritoneal cancer. The rationale for this combination includes the following: tumours with deleterious BRCA mutations or HRD express tumour-specific neoantigens, which attract PD-L1–expressing, tumour-infiltrating lymphocytes; rucaparib + anti-PD-1/PD-L1 demonstrated activity in a syngeneic ovarian cancer model; and PARP inhibitor–induced DNA damage may create a more antigenic tumour microenvironment regardless of HRD status. Trial design: Patients are required to have completed cytoreductive surgery and achieved an investigator-assessed response to frontline, platinum-based doublet chemotherapy without disease progression or rising CA-125 during frontline treatment. Patients are randomised 4:4:1:1 to receive maintenance treatment in Arm A (oral rucaparib 600 mg twice daily + intravenous [IV] nivolumab 480 mg on day 1 of every 4-week cycle), Arm B (oral rucaparib + IV placebo), Arm C (oral placebo + IV nivolumab), or Arm D (oral placebo + IV placebo). Stratification factors include centrally determined tumour HRD status, posttreatment disease status, and timing of surgery. Investigator-assessed progression-free survival (RECIST v1.1; primary endpoint) will be compared among arms. Secondary endpoints include blinded independent central review of progression-free survival, overall survival, investigator-assessed objective response rate, duration of response, and safety. Enrolment is ongoing; patients (n≈1000) will be enrolled at > 270 sites worldwide. Clinical trial identification: NCT03522246. Legal entity responsible for the study: Clovis Oncology, Inc. Funding: Clovis Oncology, Inc. Disclosure: K. Fujiwara: Research grant / Funding (institution): Advanced Oncotherapy; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Chugai-Roche; Research grant / Funding (institution): Daiichi-Sankyo; Research grant / Funding (institution): Eisai; Research grant / Funding (institution): GlaxoSmithKline; Research grant / Funding (institution): ImmunoGen; Research grant / Funding (institution): Kaken-Seiyaku; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Merck; Research grant / Funding (institution): Ono Pharmaceutical; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Shionogi; Research grant / Funding (institution): Taiho; Research grant / Funding (institution): Zeria Pharmaceutical. J-W. Kim: Research grant / Funding (institution): Clovis Oncology; Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Janssen ; Research grant / Funding (institution): Genexine; Research grant / Funding (institution): GlaxoSmithKline ; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Merck Sharp & Dohme; Advisory / Consultancy, Research grant / Funding (institution): Roche/Genentech ; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Tesaro. D.S. Tan: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Karyopharm; Advisory / Consultancy, Research grant / Funding (institution): Roche/Genentech ; Advisory / Consultancy: Genmab; Advisory / Consultancy: Merck Serono; Advisory / Consultancy: Merck Sharp & Dohme; Advisory / Consultancy: Tessa Therapeutics. N. Katsumata: Honoraria (institution): AbbVie. K. Harano: Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Chugai; Research grant / Funding (institution): Eisai; Research grant / Funding (institution): Taiho; Research grant / Funding (institution): Takeda. S. Hume: Shareholder / Stockholder / Stock options, Full / Part-time employment: Clovis Oncology. E. Jones: Shareholder / Stockholder / Stock options, Full / Part-time employment: Clovis Oncology. S. Goble: Shareholder / Stockholder / Stock options, Full / Part-time employment: Clovis Oncology. L. Sullivan: Shareholder / Stockholder / Stock options, Full / Part-time employment: Clovis Oncology. D. Shih: Shareholder / Stockholder / Stock options, Full / Part-time employment: Clovis Oncology. R.L. Coleman: Advisory / Consultancy, Research grant / Funding (institution): Clovis Oncology; Advisory / Consultancy, Research grant / Funding (institution): AbbVie; Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Esperance; Advisory / Consultancy, Research grant / Funding (institution): Janssen; Advisory / Consultancy, Research grant / Funding (institution): Millennium; Advisory / Consultancy, Research grant / Funding (institution): Merck; Advisory / Consultancy, Research grant / Funding (institution): OncoMed; Advisory / Consultancy, Research grant / Funding (institution): Roche/Genentech; Advisory / Consultancy: Bayer; Advisory / Consultancy: GamaMabs; Advisory / Consultancy: Genmab; Advisory / Consultancy: Gradalis; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Tesaro. I. McNeish: Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Tesaro. B. Monk: Advisory / Consultancy, Speaker Bureau / Expert testimony: Clovis Oncology ; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Speaker Bureau / Expert testimony: Janssen/Johnson & Johnson; Speaker Bureau / Expert testimony: Myriad; Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche/Genentech; Advisory / Consultancy, Speaker Bureau / Expert testimony: Tesaro; Advisory / Consultancy: Amgen; Advisory / Consultancy: Vermillion; Advisory / Consultancy: Verastem; Advisory / Consultancy: Precision Oncology; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Perthera; Advisory / Consultancy: NuCana; Advisory / Consultancy: Merck; Advisory / Consultancy: Mateon (formally OXiGENE); Advisory / Consultancy: Insys; Advisory / Consultancy: ImmunoGen; Advisory / Consultancy: Gradalis; Advisory / Consultancy: GlaxoSmithKline; Advisory / Consultancy: Cerulean; Advisory / Consultancy: Biodesix; Advisory / Consultancy: Bayer. R. Kristeleit: Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy: Roche; Advisory / Consultancy: Tesaro. All other authors have declared no conflicts of interest.